A Review on Indian Social Entrepreneurship - Pradhan, Bibhuti B (International Journal of Psychosocial Rehabilitation, 2019)
The idea of philanthropy has been considered to be somewhat fascinating. It provides the most appealing mix of social services and business. It's so special in nature. Entrepreneurship is typically tied to economic activity, wealth and social benefits or social stability are skilfully overlooked. Society changes have become more or less evident throughout the world in the present era of rapid industrialization and economic growth, including India with the concept of social entrepreneurship growing in India and around the world helping to represent the business more meaningfully than ever, and the spirit of entrepreneurship as it is lived. Social enterprise is not a modern term, but in recent times the idea has risen to new heights. Since Indian Government has made CSR more realistic than formality, companies are now looking for their bigger roles to help society in an economically as well as socially beneficial way. In the concept of social enterprise itself, the fine mix of capitalism and social benefits is explained. Recently, the term took new meanings and manifestations and was adopted in a broader range. This form of business was accepted by some prominent organizations in India and shaped society very positively. This is the aim of social enterprise, which is now more important than making income for society and its well-being. In the opinion of scholars, the proposal tackles also the social need and technological developments as a whole; social entrepreneurship simply considers social needs and solves them with a unique social invention. This is the differentiating between social and business enterprises, economic enterprise focuses on economic necessity, while social enterprise focuses on social needs.